The Impact of Different Classification Criteria Sets on the Estimated Prevalence and Associated Risk Factors of Diastolic Dysfunction in Rheumatoid Arthritis. (4th December 2017) - Mokotedi, Lebogang; Gunter, Sulé; Robinson, Chanel; Norton, Gavin R.; Woodiwiss, Angela J.; Tsang, Linda; Dessein, Patrick H.; Millen, Aletta M. E.
Abstract : This study compared the estimated prevalence and potential determinants of left ventricular (LV) diastolic dysfunction upon applying different classification criteria in rheumatoid arthritis (RA). LV diastolic function was assessed echocardiographically by pulsed Doppler (E / A ), tissue Doppler (E / e ′, lateral and septale ′ ), and left atrial volume index in 176 RA patients. Relationships of traditional cardiovascular risk factors and RA characteristics with LV diastolic function and dysfunction according to previous and current criteria were determined in multivariate regression models. Waist-hip ratio was associated withE / A (standardisedβ (SE) =- 0.28 ± 0.09, p = 0.0002 ) and laterale ′ (standardisedβ (SE) =0.26 ± 0.09, p = 0.01 ); low diastolic blood pressure was related toE / e ′ (standardisedβ (SE) =- 0.16 ± 0.08, p = 0.04 ). Diastolic dysfunction prevalence differed upon applying previous (59%) compared to current (22%) criteria (p < 0.0001 ). One SD increase in waist-hip ratio was associated with diastolic dysfunction when applying current criteria (OR = 2.61 (95% CI = 1.51–4.52), p = 0.0006 ), whereas one SD increase in diastolic blood pressure was inversely related to diastolic dysfunction upon using previous criteria (OR = 0.57 (95% CI = 0.40–0.81), p = 0.002 ). In conclusion, application of current and previous diastolic dysfunction criteria markedly alters the prevalence and risk factors associated with diastolic dysfunction in RA.